PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATERI TEKANAN ZAT KELAS VIII MTS PUTRI AL-ISHLAHUDDINY - Jannah, Khusnul; Irwan; Ali, Lalu Usman (CAHAYA: Journal of Research on Science Education, 2024)
This study aims to determine the effect of using a problem-based learning model on students' critical thinking skills on substance pressure material. This research is located at MTs Putri Al-Ishlahuddiny Kediri with a total of 4 classes in class VIII. The samples used in this study were 2 classes selected by simple random sampling, so that class VIII D as the experimental class and Class VIII C as the control class. This type of research is quantitative research with a quasi-experimental research approach, pretest-postest control group design type . The n-gain test results obtained in the experimental class 0, 12 and the control class -0.044 and based on the results of the hypothesis test using the independent sample t-test test that has been carried out obtained a value of 0.000. Based on the results of the n-gain test and hypothesis testing that the thinking ability of students is more improved in the experimental class so that there is an effect of using theproblem-based learning  modelon the thinking ability of students on substance pressure material.